Combined effect of genetic polymorphisms of AURKA and environmental factors on oral cancer development in Taiwan. - Chia-Hsuan Chou; Ying-Erh Chou; Chun-Yi Chuang; Shun-Fa Yang; Chiao-Wen Lin (PLoS ONE)
Background Oral squamous cell carcinoma (OSCC) is the sixth and fourth most common cause of cancer death in men worldwide and in Taiwan, respectively. AURKA, which encodes a centrosome-related serine/threonine kinase, is frequently amplified and overexpressed in many human cancers, particularly advanced OSCC. We conducted a hospital-based case-control study to estimate AURKA single-nucleotide polymorphisms (SNPs) and environmental risk factors to determine OSCC susceptibility and clinicopathological characteristics. Methodology/principal findings We enrolled a total of 876 OSCC patients and 1200 controls. Four SNPs of AURKA, namely rs1047972, rs2273535, rs2064863, and rs6024836, were analyzed using real-time polymerase chain reaction (PCR). Among the 1420 smokers, the AURKA polymorphism carriers with the betel nut chewing habit had a higher risk of oral cancer than AURKA wild-type (WT) carriers without the betel nut chewing habit. Patients with the AURKA rs2064863 gene had a 1.365-fold higher risk of stage III or IV OSCC (95% confidence interval [CI] 1.029-1.811) than those with the rs2064863 WT gene. Furthermore, carriers of the AURKA rs1047972/rs2273535/rs2064863 C-A-T haplotype had a 1.736-fold (95% CI 1.110-2.715) higher risk of OSCC than controls (C-T-T, the most common haplotype). Among patients with the betel quid chewing habit, carriers of other haplotypes (C-T-T, C-A-G, T-A-T, T-A-G, T-T-T, and C-T-G) had a 12.857-fold (95% CI 10.731-15.404) increased risk, and carriers of the C-A-T haplotype had the highest risk (AOR: 31.120; 95% CI 13.864-69.850) of OSCC, compared with those without the betel quid chewing who harbored other haplotypes. Conclusions In conclusion, betel nut chewing combined with the AURKA C-A-T haplotypes lead to a high risk of OSCC. These findings reveal a novel genetic-environmental predisposition for oral tumorigenesis.